Sex offenses, vulnerability and sexually trasmitted diseases - Reis, Jair N.; Martin, Carmen C.S.; Bueno, Sônia M.V. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Background: Establishing an asymmetric relation of power and authority the sexual violence hurts Law rules and breaks the barriers of social classes. Attacking both sexes and all age groups, it occurs so much in the private space as in the public, producing physical and psychological consequences. Besides the genital and non-genital injuries, the victims experience the possibility of the acquisition of a sexually transmitted disease and HIV. Objective: Analyze under the vulnerability point of view’s concept, characteristics related to sexual assaults and the victims’ possibility to acquire sexually transmitted diseases. Methods: We elected sexual assault incidents committed against women, categorized according to the age criterion established by the Child and Adolescent’s Statute, notified by the Police Office for Women’s Protection and examined by forensic experts of the Center for Legal Medical Investigation of Ribeirão Preto City in the period of 1996 - 2000. Results: They were 358 victimized women, being 135 children, 112 adolescents and 111 adults, through 197 rape crimes, 129 violent indecent exposures and 32 associations of these two delicts. Women were preferential victims of these crimes (91,6%) and children and adolescents the more abused (69%). Single offenders represented 83,8% of the cases and 5,9% the ones of multiple aggression. Genital and anal injuries were evidenced in 14,5% of the victims. Conclusions: Vulnerability of victims to sexually transmitted diseases results of factors as susceptibility, type of sexual contact, number of offenders, presence of genital and anal injuries, behavioral and social context.